Penetration Testing System CERDAS With Brute Force Method - Merlang, Ronald; Siswanto, Apri (oneamrd (One a Mllions Dreams Corporation), 2025)
Security of access rights is an important aspect so that there is no misuse by individuals seeking profit. The national cybersecurity operations center and the state cyber code agency recorded 88 million cyber-attacks in 2020. In an effort to prevent attacks on CERDAS, the author conducted a study by raising the problem